Benign Prostatic Hyperplasia Patients' Quality Of Life And The Severity Of Their Lower Urinary Tract Symptoms (The Review of Diabetic Studies, 2024)
Background: Benign prostatic hyperplasia (BPH) is a prevalent condition in older men, causing significant morbidity. Benign prostatic hyperplasia can lead to urinary retention, and often the presence of moderate-to-severe lower urinary tract symptoms could impact on patients’ quality of life.Aim: to assess the relation between the severity of lower urinary tract symptoms and quality of life among patients with benign prostatic hyperplasia.Research design: A descriptive correlational research design was utilized.Setting: Saudi University Hospital, Urology department.Sample: A targeted sample of sixty male patients with BPH who were experiencing lower urinary tract symptoms.Tools: tool I: A structured interview questionnaire,tool II: International Prostate Symptom Score,tool III: Benign prostatic hyperplasia - Specific Quality of life scale.Results showed that the mean age of studied patients was 51.97±4.94 years. 80% presented with grade II, according to severity of lower urinary tract symptoms, 3.30% had mild symptoms, 71.0 % had moderate symptoms, and 25.0% had severe symptoms. There was a statistically significant positive correlation between the severity of lower urinary tract symptoms and quality of life (P. value